Adsorptive transfer cyclic square-wave voltammetry and HPLC with tandem electrochemical detection - Two novel methods for determination of chili peppers pungency - Jerga, Radek; Skopalová, Jana; Barták, Petr (Talanta, 2024)
The pungency of chili peppers, the most popular hot spice used worldwide, is caused by capsaicinoids (CPDs), the content of which can vary greatly due to varietal differences and growing conditions. For the first time, a novel simple method for the fast determination of CPDs in chili peppers and chili products was developed based on adsorptive transfer cyclic square-wave voltammetry (AdTCSWV), using adsorption of lipophilic CPDs on an unmodified glassy carbon electrode surface from methanolic extracts of chili pepper samples. The CSWV is based on short oxidation of adsorbed CPDs to quinoid products, and their subsequent reduction and re-oxidation to provide specific analytical signals with a linear range from 0.05 to 1.00 mg L-1. This principle was also implemented in tandem coulometric and amperometric detection of CPDs after HPLC separation. The two-step electrochemical detection provides increased selectivity for CPDs in case of CPDs co-elution with other electrochemically oxidizable components that cannot be reversibly reduced.
Keywords: adsorpce; kapsaicin; Limit of Detection; limita detekce; elektrody; elektrochemické techniky; Chromatography, High Pressure Liquid; Capsaicin; Electrodes; vysokoúčinná kapalinová chromatografie; Adsorption; Capsicum; Electrochemical Techniques